Suvorexant for Primary Insomnia: A Systematic Review and Meta-Analysis of Randomized Placebo-Controlled Trials. - Taro Kishi; Shinji Matsunaga; Nakao Iwata (PLoS ONE)
Objective We performed a systematic review and meta-analysis of double-blind, randomized, placebo-controlled trials evaluating suvorexant for primary insomnia. Methods Relevant studies were identified through searches of PubMed, databases of the Cochrane Library, and PsycINFO citations through June 27, 2015. We performed a systematic review and meta-analysis of suvorexant trial efficacy and safety outcomes. The primary efficacy outcomes were either subjective total sleep time (sTST) or subjective time-to-sleep onset (sTSO) at 1 month. The secondary outcomes were other efficacy outcomes, discontinuation rate, and individual adverse events. The risk ratio, number-needed-to-treat/harm, and weighted mean difference (WMD) and 95% confidence intervals (CI) based on a random effects model were calculated. Results The computerized literature database search initially yielded 48 results, from which 37 articles were excluded following a review of titles and abstracts and another eight review articles after full-text review. Thus, we identified 4 trials that included a total of 3,076 patients. Suvorexant was superior to placebo with regard to the two primary efficacy outcomes (sTST: WMD = -20.16, 95% CI = -25.01 to -15.30, 1889 patients, 3 trials, sTSO: WMD = -7.62, 95% CI = -11.03 to -4.21, 1889 patients, 3 trials) and was not different from placebo in trial discontinuations. Suvorexant caused a higher incidence than placebo of at least one side effects, abnormal dreams, somnolence, excessive daytime sleepiness/sedation, fatigue, dry mouth, and rebound insomnia. Conclusions Our analysis of published trial results suggests that suvorexant is effective in treating primary insomnia and is well-tolerated.